Transient hypothyroidism in a neonate following maternal exposure to vinblastine during pregnancy: a case report and review - Amin, Zubair; Aung, Win Thu; Ng, Yvonne Peng Mei (Frontiers in Pediatrics, 2024)
BackgroundVinblastine is a widely used chemotherapeutic agent for various cancers. We report a case of transient congenital hypothyroidism following maternal exposure to vinblastine during the third trimester of pregnancy and propose possible mechanisms of action.MethodWe utilized the CARE guidelines to report the case.Case presentationThe mother is a 30-year-old previously healthy Malay woman who was diagnosed with Hodgkin lymphoma during her 28th week of pregnancy. She received two cycles of vinblastine monotherapy during her third trimester. She delivered a healthy baby girl at 37 weeks of gestation. Cord blood screening for congenital hypothyroidism and subsequent thyroid function tests showed evidence of congenital hypothyroidism. An ultrasound scan of the baby confirmed the presence of the thyroid gland, but there was no uptake of radionuclide tracer by the thyroid gland, thereby ruling out thyroid dysgenesis or dyshormonogenesis as the plausible cause of hypothyroidism. The baby was treated with replacement thyroxine for 18 months with eventual normal growth and development.ConclusionThis is the first reported case of transient congenital hypothyroidism following maternal exposure to vinblastine during the third trimester of pregnancy. Although direct causation cannot be established, heightened awareness of neonatal hypothyroidism is recommended after exposure to vinblastine or similar drugs in pregnancy.